How Does Learning Happen? Ontario’s Pedagogy of Oppression?: A Critical Discourse Analysis of Ontario’s Early Years Pedagogical Framework - Stronach, Richard A. E. (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
As Canada begins to establish universal childcare, the market-based neoliberalism of the early learning and care system continues to undervalue, underpay, overwork, and overpolice early childhood educators (ECEs). Ontario’s resource How Does Learning Happen? (HDLH) has been celebrated for its sociocultural stance and identified as transformative and central to the modernization of Ontario’s childcare system. Critical discourse analysis reveals how HDLH and the Ontario Ministry of Education continue to oppress ECEs. The implementation of universal childcare provides an opportunity for the government to include ECEs to make real changes in working conditions, wages, and the provision of quality childcare.